Palliative Care Needs Of Patients With Chronic Diseases In Family Medicine Settings: A Systematic Review (The Review of Diabetic Studies, 2025)
Background: Patients with chronic diseases such as cardiovascular, renal, respiratory, and oncological conditions frequently experience high symptom burdens and diminished quality of life, underscoring the importance of timely and integrated palliative care. Family medicine and primary care settings are uniquely positioned to address these needs, yet gaps in service delivery persist.Objective: To systematically review the evidence on the prevalence, characteristics, and outcomes of palliative care needs and interventions for patients with chronic diseases in family medicine or primary care contexts.Methods: A systematic review was conducted following PRISMA 2020 guidelines. Eligible studies included adults with chronic diseases receiving care in primary care or community settings, published in English between 2010 and 2024. Fifteen studies were included, covering randomized controlled trials, cohort studies, cross-sectional analyses, and mixed-method designs.Results: Across populations and settings, patients exhibited significant unmet palliative care needs, particularly related to symptom management, psychosocial distress, and functional decline. Interventions such as integrated palliative and disease-specific care models improved quality of life, reduced symptom burden, and, in some cases, decreased hospitalizations. However, not all studies demonstrated reductions in healthcare utilization, and barriers related to provider readiness, service infrastructure, and late referrals were consistently reported.Conclusion: Integrating palliative care into family medicine pathways offers measurable benefits for patients with chronic diseases. Sustainable implementation will require workforce training, systemic support, and policy frameworks that embed palliative care within chronic disease management strategies.